Can respiratory muscle training change the blood pressure levels in hypertension? A systematic review with meta‐analysis. (16th March 2021) - da Silva, Claudio D.; de Abreu, Raphael M.; Rehder‐Santos, Patrícia; De Noronha, Marcos; Catai, Aparecida M.
Abstract : The aim was to systematically review randomized controlled trials investigating the effects of respiratory training on blood pressure control in hypertensive individuals. Systematic review with meta‐analysis was coducted following the guidelines from PRISMA statement. Searches for randomized controlled trials were performed in four electronic databases (PubMed, Cochrane Library, SCOPUS, and PEDro). Studies were included if they were randomized controlled trials that examined the impact of respiratory training on blood pressure of individuals with systemic arterial hypertension and the patients had no other associated disease. Eight studies were included for final analysis (total of 270 participants; 18–85 years) and presented an average score of 6.25 in the PEDro scale, being considered of high methodological quality. The meta‐analysis showed a reduction in systolic and diastolic blood pressure for respiratory training when the load was applied [−15.72 (−18.63; −12.81) and −7.08 (−9.03; −5.13) mmHg, respectively]. There was also a reduction in systolic, but not in diastolic blood pressure when the training was performed without load [−5.08 (−7.49; −2.66) and −1.04 (−2.55; +0.46) mmHg, respectively]. The respiratory training has a positive effect in BP in hypertensive patients, however, only when performed with load seems to be able to promote some beneficial effect on diastolic blood pressure reduction.